A Mathematical Model For The Effects of Volume Fraction and Fiber Aspect Ratio of Biomass Mixture During Enzymatic Hydrolysis - Norazaliza, Jamil; Wang, Qi (Institute of Physics Publishing, 2017)
Renewable energy or biofuel from lignocellulosic biomass is an alternative way to replace the depleting fossil fuels. The production cost can be reduced by increasing the concentration of biomass particles. However, lignocellulosic biomass is a suspension of natural fibres, and processing at high solid concentration is a challenging task. Thus, understanding the factors that affect the rheology of biomass suspension is crucial in order to maximize the production at a minimum cost. Our aim was to develop a mathematical model for enzymatic hydrolysis of cellulose by combining three scales: the macroscopic flow field, the mesoscopic particle orientation, and the microscopic reactive kinetics. The governing equations for the flow field, particle stress, kinetic equations, and particle orientation were coupled and were simultaneously solved using a nite element method based software, COMSOL. One of the main results was the changes in rheology of biomass suspension were not only due to the decrease in volume fraction of particles, but also due the types of fibres. The results from the simulation model agreed qualitatively with the experimental findings. This approach has enables us to obtain better predictive capabilities, hence increasing our understanding on the behaviour of biomass suspension.